Application of Controlled Switching to Reduce Switching Over-voltages on EHV Transmission Lines - Munzir Mohamed Adham Ali; El-Amin Hamoda Dabee; Kamal Ramadan Doud (University of Khartoum Engineering Journal, 2025)
This work is an investigation into the effectiveness of controlled switching techniques in reducing switching over voltages on EHV transmission lines. The case study is the Sudanese 500 kV transmission line connecting generation at Merawi to the load centre at Khartoum (Sudan). The method used is modeling and simulation the line using MATLAB/SIMULINK. The results show that the phase-controlled switching technique is far superior to the Pre-insertion Resistor (PIR) method. It is also found that switching over-voltages are very much reduced when Metal-Oxide Surge Arresters (MOSA) are installed at the line ends and also when the transmission line is compensated.